Hif1a inactivation rescues photoreceptor degeneration induced by a chronic hypoxia-like stress. Issue 12 (December 2018) - Barben, Maya; Ail, Divya; Storti, Federica; Klee, Katrin; Schori, Christian; Samardzija, Marijana; Michalakis, Stylianos; Biel, Martin; Meneau, Isabelle; Blaser, Frank; Barthelmes, Daniel; Grimm, Christian
Abstract Reduced choroidal blood flow and tissue changes in the ageing human eye impair oxygen delivery to photoreceptors and the retinal pigment epithelium. As a consequence, mild but chronic hypoxia may develop and disturb cell metabolism, function and ultimately survival, potentially contributing to retinal pathologies such as age-related macular degeneration (AMD). Here, we show that several hypoxia-inducible genes were expressed at higher levels in the aged human retina suggesting increased activity of hypoxia-inducible transcription factors (HIFs) during the physiological ageing process. To model chronically elevated HIF activity and investigate ensuing consequences for photoreceptors, we generated mice lacking von Hippel Lindau (VHL) protein in rods. This activated HIF transcription factors and led to a slowly progressing retinal degeneration in the ageing mouse retina. Importantly, this process depended mainly on HIF1 with only a minor contribution of HIF2. A gene therapy approach using AAV-mediated RNA interference through an anti-Hif1a shRNA significantly mitigated the degeneration suggesting a potential intervention strategy that may be applicable to human patients.